Cultural Dimensions and Sustainable Stock Exchanges Returns in the Asian Region - Susilo Nur Aji Cokro Darsono; Wing-Keung Wong; Nguyen Tran Thai Ha; Hafsah Fajar Jati; Diah Setyawati Dewanti (Universitas Muhammadiyah Yogyakarta, Indonesia, 2021)
Research aims: The aim of this paper is to examine the effect of four cultural dimensions such as power distance index (PDI), individualism (IDV), uncertainty avoidance index (UAI), and long-term orientation (LTO) on the sustainable investment return in Asian sustainable stock exchanges.Design/Methodology/Approach: Quantitative research method was applied for this research. Monthly sustainable stock indices from seven Asian countries for the period 2015-2019 were considered. This research employed the Ordinary Least Square (OLS) regression and Feasible Generalized Least Square (FGLS) regression with id and time fixed effect.Research findings: The outcomes of our empirical investigation underlined the fact that: (i) an increase in power distance (PDI) would increase the market returns in the Asian region; (ii) individualism (IDV) had a positive and significant impact on the market returns, and the increase of individualism in the Asian countries would lead to the higher sustainable stock returns; (iii) increase in the uncertainty of avoidance (UAI) by investors in the Asian region would lead to the higher stock returns; (iv) the long term orientation (LTO) had a significant and positive impact on market returns. It showed that if the investor had a long-term orientation on the sustainable stock exchange in the Asian region, it would lead to increased stock returns.Theoretical contribution/Originality: This research's theoretical contribution is to present the causal relations of cultural differences on the sustainable investment return in the Asian region.Practitioner/Policy implication: This research’s implication is to increase the concern of individual investors, portfolio managers, and investment companies regarding the cultural dimension effect on sustainable investment.Research limitation/Implication: The limitations still exist in this research, such as: (1) limited data for sustainable stock indices in the Asian region; (2) this research mainly focused on four cultural dimensions instead of six dimensions in Hofstede's model; (3) the future research should include the control variables and some other financial variables related with the sustainable investment.